Error Analysis On Written Production By The Second Year Students Of SLTP Negeri 1 Purwantoro Wonogiri In 2003/2004 - Raharjo, Didik Hariyadi, Dra. Endang Fauziati, M.Hum, Dra. Siti Khuzaimah (2013)
The aims of this study are to find out the types of errors made by the students in their compositions, the dominant type of errors, the frequency of errors, the sources of errors and the proposed remedial teaching. The research was carried out on June, 26th 2004. The research was conducted to the second years students of SLTP Negeri 1 Purwantoro in 2003/2004, especially class B, which has 40 students. Dealing with the research instrument for collecting the data, the writer used a test, that is composition test. From the result of the test the writer gets the data to be analyzed. The collected data, then were analyzed descriptively by means of error analysis, which proceeded from identifying the data, describing, and explaining the errors. From the computation of errors, there are 110 errors made by the students. Those errors can be divided into four types of errors. There are 37 number of Omission error (33,64%), 36 number of Misformation error (32,73%), 20 number of Misordering error (18,18%) and 17 number of addition error (15,45%). The highest frequency of errors are Omission error (33,64%), while the lowest frequency of errors are Addition error (15,45%).